Invited correspondence on ‘Fissureless fissure-last video-assisted thoracoscopic lobectomy for all lung lobes: a better alternative to decrease the incidence of prolonged air leak?’ - Stamenovic, Davor (Journal of Thoracic Disease, 2018)
At the time I was initiating this study (1), I wasn’t aware of other studies on fissureless fissure-last technique. More precisely, as I start operating with this technique, especially for non-upper lobes, I was trying to solve a basic technical problem that I was facing from time to time, thinking I might have been the first to do so.